Map of Thematic Learning at Elementary School in the Pandemic Period (Study at Jakarta, Depok, dan Tangerang Areas) - Suharsiwi Suharsiwi; Suradika Suradika; Fatma Nurmulia (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The Implementation of online thematic learning during the Covid-19 pandemic created significant obstacles for teachers, students and parents. This research is focused on the implementation of thematic learning in elementary schools. This research is focused on the implementation of thematic learning in elementary schools in the DKI Jakarta, Depok, and Tangerang areas, with research sub-focus: 1) Teachers' understanding of implementing thematic learning in elementary schools, 2) Teacher obstacles in implementing thematic during a pandemic. Research using descriptive qualitative research. The survey was conducted on 48 teacher respondents, namely class I and II teachers in five schools in the Jakarta, Depok and Tangerang areas. Data collection was carried out through focus group discussions between researchers, teachers and school principals. The results showed that the teacher's constraints in carrying out thematic learning were teaching materials, time constraints, and when online learning was not optimal so that when offline they had to repeat lessons given online. The implication of this research is that it can provide information and knowledge for education practitioners in implementing ideal online learning and obstacles during the Covid-19 pandemic, so that it can be a way out if similar obstacles occur in the future.